Mednarodno investicijsko pravo, arbitraža in Petišovci - Turšič, Domen (Podjetje in delo, 2020)
In July 2020, Ascent Resources plc sent a Notice of Dispute to Slovenia and thus made the first formal step in presenting a claim for compensation before an international investment tribunal. After an overview of two treaties that will be the basis of the tribunal`s jurisdiction should the arbitration proceedings commence, the article focuses on aspects of two investment protection standards relevant in the present case: fair and equitable treatment and the non-impairment clause. Through an analysis of investment treaty case law, the article focuses on the content of states` obligations and the standard of proof the investor must satisfy in order to prevail with its claim. The article also focuses on defence arguments available to states, flowing from the principle of sovereignty.
Keywords: environmental protection; fair and equitable treatment; international investment arbitration; international investment law; mednarodna investicijska arbitraža; mednarodne pogodbe; mednarodno investicijsko pravo; nerazumno in diskriminatorno ravnanje; non-impairment clause; poštena in pravična obravnava; sovereignty; suverenost; treaties; varovanje okolja